Pattern formation in Lepidopteran wings - Sekimura, T; Maini, P; Nardi, J; Zhu, M; Murray, J (1998)
Two different kinds of patterns have been studied in lepidopteran wings - color pattern and the spacing pattern of scale cells. These patterns exist on two different spatial scales. In the early stages of adult development, precursors of scale cells differentiate throughout each epithelial monolayer and migrate into rows that are roughly parallel to the body axis and regularly spaced about 50 mum apart. We develop a mathematical model for the formation of these parallel rows of scale cells in the devleoping adult wings of Lepidoptera. We show that the inclusion of biologically realistic adhesive properties of cells, as specified by their positions, is sufficient to generate in a robust manner a series of scale rows along the length of the wing in the correct orientation. We next look briefly at the biology of color pattern formation, and we review some mathematical models for this phenomenon, which, in contrast to the spatial arrangement of scale cells, involves interactions among cells that operate over longer distances.